The Porosity of Stabilized Earth Blocks with the Addition Plant Fibers of the Date Palm - Abdelghani Idder; Abdelmadjid Hamouine; Boudjemaa Labbaci; Rabia Abdeldjebar (Salehan Institute of Higher Education, 2020)
This work is an experimental study to analyze the physical behavior of Stabilized Earth Block (SEB) and reinforced with Plant Fibers of the Date Palm (PFDP). This is part of the valorization of local building materials (earth, fiber) and contributes to reduce the price of housing. Initially, physical tests (Density, Total Water Absorption, and Capillary Absorption) were carried out in preparation for the porosity study. However, the main objective of this study is the investigation of porosity phenomenon using several methods as well as the total porosity estimation, the total volume porosity in water and Open porosity methods, where the mechanical resistance is also considered. In order to improve the stabilized earth block porosity analyses, various dosages are proposed for cement, lime and fiber. Thus (0%, 5%, 10%) of cement, (0%, 5%, 10%) of lime and the combination (5% cement + 5% lime) with (0%, 0.25%, and 0.5%) of fibers for each composition. The experimental results showed that the addition of fibers increases the porosity of the stabilized earth block proportionally and an increasing quantity of the stabilizer reduces the porosity of the SEB, cement is also more effective at closing pores than lime. Moreover, the compositions 10% cement and the mixture of 5% cement + 5% lime with 0% fiber showed a good results of porosity, for this reason they can be used as a durable building material and good resistance to natural and chemical aggression.